A brief account of river rehabilitation experiences - ., Md Nuruzzaman; Al Mamun, Abdullah; Salleh, Md Noor (IIUM Press, 2017)
Rivers are vital water resources which are being altered due to urbanization and industrialization, causing threats to the environment. As a result, rehabilitation of polluted rivers has gained great importance during the last century in many countries of the world. Literature on river rehabilitation projects has been reviewed in this paper, highlighting the experiences gathered in the developed nations of the world; such as the USA, the UK, Japan, etc. Rehabilitation issues of the rivers crossing borders have also been discussed in this paper. Key lessons from different experiences in different regions have been extracted and a comparison has been made. Summarised statistics on different experiences also have been presented. Finally, some guidelines have been provided based on various experiences, which should be helpful for developed and developing nations while making their river rehabilitation efforts.